Efforts to Enhance the Entrepreneurial Spirit of Small Business Owners and Craftsmen in Karangdoro Village, Tegalsari, Banyuwangi Regency - Muhamad Annas; Nurul Inayah (Simfoni Ilmu Cindekia, 2025)
This community service program to enhance the entrepreneurial spirit of small businesses and artisans in Karangdoro Village, Tegalsari, Banyuwangi Regency aims to provide training and mentoring in developing entrepreneurial skills, business management, and increasing production capacity. Karangdoro Village, where the majority of its residents are engaged in small businesses and crafts, faces challenges in marketing, financial management, and product innovation. This program is designed to provide a better understanding of the importance of business planning, cost efficiency, and effective marketing strategies, both offline and online. Furthermore, mentoring is provided to introduce digital technologies that can help improve market access and operational efficiency. Through a participatory approach, it is hoped that small businesses and artisans can increase their competitiveness, expand their market networks, and increase income. The results of this community service program indicate an increase in participants' understanding of entrepreneurial management and their success in implementing more modern and effective marketing strategies, which have positively impacted the stagnation of their businesses. This training and mentoring is expected to stimulate local economic growth and strengthen the role of small businesses in the Karangdoro Village economy.